DNA damage and repair in Anguilla anguilla L. exposed to pesticides - Marques, Ana Margarida Lourenço Silva (2013)
The presence of pesticides in water bodies is a worrying environmental issue, occurring mainly due to spray-drift, surface runoff or inadvertent applications. This vast class of agrochemicals is known to induce several pernicious effects in non-target aquatic organisms, namely fish. However, data concerning the genotoxic impact of these compounds are scarce. Hence, the present thesis aimed to fill the knowledge lacuna on pesticides capacity to induce genotoxicity to fish, addressing two commercial formulations: Decis®, a deltamethrin-based insecticide, and Roundup®, a glyphosate-based herbicide, each representing a widely used class of biocides. The present work aimed to assess: (i) the chromosomal damaging potential of Decis®, (ii) the DNA damage induction by Roundup®, (iii) the involvement of oxidative processes on the DNA integrity loss as well as (iv) the involvement of DNA repair system in the progression of the DNA damage induced by Roundup®. European eel (Anguilla anguilla L.) was adopted as test organism, performing short-term exposures of 3 days to environmentally realistic concentrations of Decis® and Roundup® and post-exposure evaluations of 1, 7 and 14 days to assess the damage evolution in pesticide-free water. In order to assess the genotoxic damage induced by Decis®, the erythrocytic nuclear abnormalities (ENA) assay was performed, evaluating chromosomal damage, a hardly repairable type of lesion. In what concerns to Roundup® experiment, the comet assay was adopted as genotoxic endpoint, measuring DNA damage as strand breaks, able to be repaired. In order to assess the involvement of oxidative damage in Roundup®-induced genotoxicity, the comet assay was performed with an extra step, where nucleoids were digested with the endonucleases formamidopyrimidine DNA glycosylase (FPG) and endonuclease III (EndoIII), measuring oxidized purines and pyrimidines, respectively. The base excision repair (BER) assay was adopted to evaluate the oxidative DNA damage repair ability of eels exposed in vivo to Roundup®. In general, Decis® and Roundup® demonstrated their genotoxic induction to A. anguilla, since they induced cytogenetic and DNA damage, respectively. In both cases, the damage showed to be of transient nature, since fish were able to completely reverse the previously induced damage. Decis® demonstrated its genotoxic potential by the increase of erythrocytic nuclear abnormalities frequency as a result of its clastogenicity and/or aneugenicity properties. Cytogenetic damage values of exposed eels returned to control levels after 7 days in insecticide-free water. This recovery appeared to be mainly a result from a preferential removal of cells with abnormal nuclear morphology, since no alterations were noticed at the erythropoiesis dynamics. Roundup® was capable of inducing DNA damage in hepatic cells and, though not directly reflected in an increase of breaks at FPG- and EndoIIIsensitive sites, the involvement of oxidative processes in Roundup® genotoxicity was confirmed. The DNA damage values of exposed eels returned to control levels after 1 day in herbicide-free water, mainly due to the repairable condition of this type of damage and the cessation of the exposure. DNA repair enzymes seem to be susceptible to inhibitory actions associated to higher levels of Roundup® constituents/metabolites and/or ROS likely to occur in liver during the exposure period. However, in the postexposure period, an increased capacity to repair oxidative DNA damage emerged, being a crucial pathway for the complete recovery from the genetic damage induced. Evaluating the performance of the genotoxic endpoints adopted in the present study, ENA and comet assays revealed to be suitable to detect the described types of damage. In addition, it became clear that both should be used as complementary tools, since each one measures specific damage types that might be detected at different moments concerning exposure/postexposure periods. In what concerns the management/monitoring practices of pesticides use, the present thesis demonstrated that aquatic biota is under substantial threat and provided useful data to develop stricter regulatory directives. Further studies on this subject should be encouraged, contributing to the increased knowledge and the assessment of the environmental risk to fish populations. In addition, it should be investigated the real impact of pesticides, considering the fish ability to rapidly reverse the short-term effects. This might help the establishment of stricter regulatory procedures aiming the reduction of pesticides overuse and/or inadvertent applications as well as the choice of less toxic compounds.